2018
DOI: 10.13165/vpa-18-17-2-06
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Anotacija. Tvaraus vystymosi teorija yra svarbiausia koncepcija, kuria remiantis pastaraisiais dešimtmečiais yra formuojama ilgalaikė žemės ūkio politika Europos Sąjungos ir kitose išsivysčiusiose šalyse. Taikant šią teoriją praktikoje, susiduriama su iššūkiais, kylančiais iš tvaraus vystymosi tikslų integralumo. Skirtingi įvairių šalių pasiekimai rodo, kad tvaraus vystymosi politikos veiksmingumas priklauso ne tik nuo to, kaip įvairaus lygmens institucijos sugeba suderinti aplinkosauginius, socialinius ir eko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Based on the scientific literature analysis, a list of sustainability indicators was compiled, where each indicator is traditionally assigned to one of the sustainability domains. However, the interviews also examined the complexity of the indicators, as it is generally assumed that the links between these dimensions of sustainability are compatible and mutually supportive [29,31]. The results of this study showed that economic, social, and environmental effects are interconnected.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Based on the scientific literature analysis, a list of sustainability indicators was compiled, where each indicator is traditionally assigned to one of the sustainability domains. However, the interviews also examined the complexity of the indicators, as it is generally assumed that the links between these dimensions of sustainability are compatible and mutually supportive [29,31]. The results of this study showed that economic, social, and environmental effects are interconnected.…”
Section: Discussionmentioning
confidence: 88%
“…Since the definition of the concept of sustainable development, it has become an important theoretical approach for assessing various processes in agriculture [31][32][33]. This methodological approach is also used for studies that analyze the experience of agricultural digitalization.…”
Section: Theoretical Frameworkmentioning
confidence: 99%